Media Pembelajaran dengan Powerpoint Sebagai Instrumen Pembelajaran untuk Sekolah Menengah Kejuruan - Muldi Yuhendri; Simon Padri P (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This study aims to produce valid and practical Powerpoint media in basic electricity and electronics subjects in class X (SMKN) 5 Padang. To achieve this goal, the authors develop the media using research and development methods with the following steps : (1) analyzing the need to determine the problem, (2) determining KD in determining material needs, (3) defining concepts, (4) analyzing students which is an analysis of student characteristics, (5) sketching, (6) collecting media objects, (7) making media designs, (8) expert validation stage, (9) revision based on expert validation, (10) trial phase. The development results show that Powerpoint media is proven to be very valid. The test results gave the validity value carried out by the validator of 0.91 from the expected score to be in the valid category, while the practicality test carried out by the subject teacher gave a value of 94.2% of the score which was expected to fall into the very practical category. The results of this study indicate that learning media with Powerpoints made for basic electricity and electronics subjects are suitable for use as learning resources.